The Bidirectional Relationship Between Depressive Symptoms and Homebound Status Among Older Adults. (25th January 2018) - Xiang, Xiaoling; An, Ruopeng; Oh, Hyunsung
Abstract: Objectives: This study aimed to examine the bidirectional relationship between depressive symptoms and homebound status among older adults. Method: The study sample included 7, 603 community-dwelling older adults from the National Health and Aging Trends Study. A bivariate latent state-trait model of depressive symptoms and homebound status was estimated via structural equation modeling. Results: The model fit the data well (Root Mean Square Error of Approximation = .02, Comparative Fit Index = .97, Standardized Root Mean Square Residual = .06). The relationship between homebound status and depressive symptoms can be decomposed into three parts: a moderate correlation between the stable trait components ( r = .56, p <.001); a contemporary association of the state components ( b = .17, p <.001); and bidirectional lagged effects between the state components. Change in homebound status was as a stronger predictor of depressive symptoms ( b = .19, p < .001) than change in depressive symptoms was of homebound status ( b = .06, p < .001; test of difference: Δ scaled χ 2 (1) = 24.2, p < .001). Discussion: Homebound status and depressive symptoms form a feedback loop to influence each other. Improving the outdoor mobility of older adults may have immediate benefits for reducing depressive symptoms.